Power unified spatial information model for smart grid dual complex network - Huihui LIU; Chengyue YANG; Lisha WU; Yiying ZHANG (Dianxin kexue)
Smart grid refers to the next generation power grid in which the electricity distribution and management are upgraded by combining the power grid and power communication network（called dual network）.According to the problems,such as the power spatial information sharing of multi-business integration problem,the thematic application and the dynamic display etc,the new power unified spatial information model（PUSIM）was proposed for smart grid dual network.Based on the abstract layer,entity layer and business layer,PUSIM builded the geometric object,topology relationship and the conceptual model and logical model of account property for the dual network,and constructed the unified model,expression and integration management for the dual network based on common information model.